KERAPATAN VEGETASI BERDASARKAN TEMPERATUR UDARA MENGGUNAKAN CITRA LANDSAT 8 DI KECAMATAN ULUJADI KOTA PALU - Priyana, Haris; Hamzari, Hamzari; Arianingsih, Ida; Hamka, Hamka (Universitas Tadulako, 2018)
Palu City is the Capital of Central Sulawesi Province, which is also the center of a variety of activities and services for both residents within the city and other areas outside or around the City. Activities and services of the population have resulted in the city of Palu experiencing very rapid development. The rapid growth of settlements and development in the city of Palu will have a significant influence on land use change. Changes in land use that are not in accordance with the rules of spatial planning can result in decreased environmental quality, environmental degradation / environmental damage and reduced natural resources. The declining quality of the environment is due to the increasingly spatial allocation of space for urban vegetation. The purpose of this study was to determine the level of air temperature distribution in Ulujadi District based on Landsat 8 imagery and determine the level of vegetation density based on air temperature. This research was conducted for 3 months from February to May 2016. Analysis of air temperature using band 11 to analyze the distribution of air temperature by comparing the vegetation density analysis of NDVI (Nomalized Difference Vegetation Index) using band 5 (NIR) and band 4 ( Red) on Landsat 8 imagery to determine the effect of vegetation absorption on air temperature by using ArcGIS software version 10.2. Based on the analysis of air temperature using Landsat 8 imagery, it can be concluded that the distribution of air temperatures in Ulujadi District ranged from 18.89 - 25.890C with an area of 1954.48 Ha (31%), 25.90 - 32.890C with an area of 2.198 , 67 Ha (35%), and the highest temperature distribution in Ulujadi District reached 2,213.83 Ha (35%) with an air temperature level of 32.90 - 39.890C. The level of vegetation density in Ulujadi Subdistrict is divided into three with a vegetation index value of -0.19 - 0.25 sparse density, with a distribution area of 1,381.79 Ha (22%), moderate density 0.25 - 0.35 medium density with the distribution area is 965.57 Ha (15%), the density of the meeting is 0.35 - 0.60 with a distribution area of 4.018.80 Ha (63%) from the area of Ulujadi Subdistrict.